2013
DOI: 10.4103/0019-557x.114992
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the association between periodontal disease and pre-term births among general dentists, general medical practitioners and gynecologists

Abstract: In the recent decades, periodontal disease has been identified as a risk factor for pre-term deliveries. Hence, it is important to evaluate the awareness of health-care providers of the association between periodontal diseases and pre-term birth. A self-administered questionnaire was distributed to random samples representing general medical practitioners (GMPs), general dental practitioners (GDPs) and Gynecologists for this study. A knowledge score was calculated for correct answers to 11 survey questions rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 5 publications
5
27
0
7
Order By: Relevance
“…This could be due to a lack of understanding about the importance of oral health in a holistic approach to patient care or the existence of a belief that they possess the appropriate knowledge concerning oral health. For example, Tarannum et al [29] found more general dental practitioners were aware of the association between periodontal disease and pre-term births than general medical practitioners and gynecologistS. Similarly, another study found dentists or health professionals with specialized training had more favorable attitudes towards pregnant women's oral health compared to obstetricians/ gynecologists and nurses [30,31].…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…This could be due to a lack of understanding about the importance of oral health in a holistic approach to patient care or the existence of a belief that they possess the appropriate knowledge concerning oral health. For example, Tarannum et al [29] found more general dental practitioners were aware of the association between periodontal disease and pre-term births than general medical practitioners and gynecologistS. Similarly, another study found dentists or health professionals with specialized training had more favorable attitudes towards pregnant women's oral health compared to obstetricians/ gynecologists and nurses [30,31].…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Entre un 24 y 40 % de profesionales encuestados no recomiendan procedimientos tales como las exodoncias, tratamiento de conductos y la toma de radiografías dentales durante la gestación, dato similar al informado por Tarannum et al (15), donde los profesionales encuestados manifestaban en un 50 % la inseguridad de los Rx dentales en la gestante y las exodoncias en 56 %, y en el estudio de Araujo et al (21) donde el 25,3 % de los profesionales encuestados manifestaron que las radiografías dentales estaban contraindicadas.…”
Section: Discussionunclassified
“…Se ha informado que la educación para la salud que hacen los profesionales influye favorablemente sobre los conocimientos, las actitudes y el comportamiento de los individuos, grupos y colectividades (13,15). Sin embargo, algunos estudios han identificado la necesidad de capacitación en temas de salud oral con brechas incluso del 75 % entre los ginecoobstetras (16).…”
Section: Introductionunclassified
“…Biz de bu bilgilerden yola çıkarak çalıĢma popülasyonumuzu üç birimin uzman hekimlerinden oluĢturduk. Literatürde, diyabet ve peri-odontal hastalık arasındaki iliĢkiye yönelik endokrinoloji ve metabolizma hastalıkları ile iç hastalıkları uzmanlarının ve tıp hekimlerinin farkındalığının ve hastaya yaklaĢımlarının araĢtırıldığı benzer çalıĢmalar [14][15][16][17]20 , kardiyovasküler hastalık ve periodontal hastalık arasın-daki iliĢkiye yönelik kardiyoloji uzmanlarının farkında-lığının ve hastaya yaklaĢımlarının araĢtırıldığı bir çalıĢma 23 ,kadın hastalıkları ve doğum uzmanlarıyla ve tıp hekimleriyle yapılan, olumsuz gebelik sonuçları ve periodontal hastalıklar arasındaki iliĢkiye dair hekimlerin farkındalığının ve hastaya yaklaĢımlarının araĢtır-ıldığı benzer çalıĢmalar 10,13,19,21 vardır. Ülkemizde ise, periodontal durum ve sistemik hastalıklar arasındaki iliĢkiye yönelik tıp hekimleri ile yapılan tek bir çalıĢma mevcuttur; ancak çalıĢma popülasyonu homojen değildir (pratisyen hekimler, intern, uzman hekim).…”
Section: Discussionunclassified
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Fakat ülkemizde bu konuyla ilgili çalıĢma sayısı oldukça sınırlıdır. Bu bilgilerin ıĢığında biz de çalıĢmamızda, alanında uzman tıp hekimlerinin hastalarında ağız sağlığı ile ilgili izledikleri yaklaĢımları ve periodontal durum ile sistemik durum arasındaki iliĢkiye yönelik farkındalıklarını değerlendir-meyi hedefledik.…”
Section: Introductionunclassified